Регіональна, релігійно-етнічна та соціально-демографічна характеристика континентальної еміграції з Польщі в 1930-х рр. - Шваб, Анатолій; Shvab, Anatoliy (Східноєвропейський національний університет ім. Лесі Українки, 2013)
У статті відтворено динаміку міграційних процесів між Польщею та європейськими країнами в 1930-х рр.; здійснено кількісний та структурний аналіз по роках та країнах еміграції у розрізі воєводств і віросповідань; відтворено соціально-демографічну структуру та регіональні особливості континентальної еміграції.This article is devoted to the migration movement in the 1930th in Poland. The author has analyzed the dynamics of the emigration and reemigration movement; the influence on the emigration activity of the world economic crisis and economic situation of the immigration countries; the geography of emigration to the European countries; religious, ethnic and demographic structure of emigration; regional peculiarities of the directions and religious and ethnic structure of the continental emigration. It is analyzed that due to the results of the established state policy the main contingent of the season emigration consisted of the West and Central Polish provinces population (mostly Roman Catholics) at the same time the intercontinental - of the East Polish provinces population (mostly Orthodox, Greek Catholics Jews and Evangelists).
Regional, Religious, Ethnic and Social-Demographic Characteristic of the Continental Emigration from Poland in 1930t
Keywords: еміграція з Польщі; національна структура міжвоєнної еміграції з Польщі; напрямки еміграції з Польщі; рееміграція до Польщі; еміграція у розрізі воєводств; emigration in Poland; national structure of the interwar emigration from Poland; the directions of the emigration from Poland; remigration to Poland; emigration according to the provinces